Signaling of insulin secretion by pancreatic β cell. A review (Gaceta de Ciencias Veterinarias, 2018)
Substances such as glucose, free fatty acids and amino acids are metabolized in the β cell when their intracellular concentrations reach certain levels to provide regulatory metabolic coupling factors (R-MCF) and effector (E-FCM). The R-MCF (eg, citrate, NADH/NAD+, malonyl-CoA, GTP, acyl compounds CoA long chain, glutamate, adenine nucleotides), directly or indirectly improve the production of E-MCF (eg, ATP, cAMP, monoacylglycerol, NADPH, ROS, acyl-CoA short-chain compounds), which have a direct impact on the exocytosis of insulin granules. The E-MCF activate the final components of the machinery of exocytosis, including the K+ATP/SUR1/Ca2+, Munc13-1 channel, among others, initiating insulin release. However, in order to prevent excessive secretion of insulin, β cells are also equipped with mechanisms that control excessive production of R-MCF and MCF-E. These mechanisms include metabolic pathways which act as negative modulators (AMPK, palmitoiltransferasa I carnitine, glucose-6-phosphatase, and uncoupling proteins 2, which decreases the generation of R-MCF, and signals controlling the levels of E-MCF. Thus, knowledge of some update signaling pathways involved in insulin secretion is important to better understand the pathogenesis of type 2 diabetes mellitus, where, in addition, oxidative stress plays a significant role. Finally it is considered, an important research area as it can generate new insights into the molecular pathogenesis of hyperglycemia and identify pharmacological targets for treatment and/or prevention of long-term diabetic complications.
Keywords: Insulin, MCF, oxidative stress